Hormonal influence on bone remodeling and its implications for the pathophysiology of osteoporosis - Manolagas, Stavros (Henry Stewart Talks, 2007)
Birth and fate of osteoblasts and osteoclasts, Mechanical loading, Role of osteocytes in mineralization, Sclerostin, The cell number concept, Osteoporosis, Anti-osteoporotic effects of sex steroids and their cellular mechanisms, Transcriptional regulation by estrogens, Glucocorticoid-induced bone disease, Glucocorticoids induce osteocyte apoptosis, Effects of thyroid hormones on the skeleton, Involutional osteoporosis, Age-dependent skeletal deterioration, Age-associated oxidative stress, Future implications
Updated at 2020/05/21